P399 Vedolizumab therapy results in reduced hospitalisation and steroid use over 1-year: Results from the Scottish vedolizumab consortium. (16th January 2018) - Plevris, N; Chuah, C S; Allen, R; Baker, P; Brennan, P; Churchhouse, A; Donoghue, E; Gaya, D; Jafferbhoy, H; Jenkinson, P; Jones, G; Macdonald, J; et al.
Abstract: Background: Whilst the GEMINI trials and an increasing body of real-world data have demonstrated the effectiveness and safety of vedolizumab (VDZ) in IBD, there are limited available data about the effect on hospitalisations and steroid use. Our aim was to address this in a large real-world cohort of IBD patients from across Scotland. Methods: A multicentre retrospective cohort analysis of medical records was carried out at 7 Scottish healthcare trusts. Our primary outcomes were hospitalisation rates and overall steroid use in patients remaining on VDZ. Secondary outcomes were safety and intention to treat steroid free remission rates / mucosal healing in patients with active disease. All data were prospectively collected as part of routine clinical care. Baseline demographics, clinical severity scores (HBI or Partial Mayo), faecal calprotectin (FC), endoscopy, and radiology at 3, 6, and 12 months was recorded where available. Active disease was defined as endoscopic or radiographic evidence of disease or FC >200 μg/g. Clinical remission was defined as HBI<5 or Partial Mayo <2. Biochemical remission was defined as FC <200 μg/g. Mucosal healing was determined radiologically when endoscopy was not possible. Results: A total of 340 (137 UC and 203 CD) patients were included in the primary analysis. Hospitalisation rates per patient-year were 0.60, 0.67, 0.36, and 0.16 at baseline, 3, 6, and 12 months of treatment respectively. Total number of hospitalisations reduced by 52.5% from 204 (12 months prior to VDZ) to 97 (12 months after VDZ). Proportion of patients on concomitant steroids reduced from 39.7% to 16.7% ( n = 332), 8.1% ( n = 270), 9.3% ( n = 194) at 3, 6 and 12 months respectively. In patients with active CD ( n = 153, 75.4%) steroid free clinical and steroid free biochemical remission rates were; 54.4% and 30.2% at 3 months; 47.7% and 32.1% at 6 months; 28.6% and 33.9% at 12 months. In patients with active UC ( n = 112, 81.8%) steroid free clinical and steroid free biochemical remission rates were; 57.4% and 40.9% at 3 months; 51.6% and 39.1% at 6 months; 37.5% and 41.2% at 12 months. Cumulative mucosal healing for CD and UC was 46.3% ( n = 54) and 44.4% ( n = 45) by 12 months respectively. Our cohort received >2066 VDZ infusions, 2 (0.6%) patients developed infusion reactions, 9 (2.6%) patients developed serious infections and 17 (5.0%) serious adverse events. Conclusions: VDZ is associated with reduced hospitalisation and steroid use. Steroid free remission rates, mucosal healing and safety profile were in keeping with the published literature.